2022
DOI: 10.25115/ejrep.v20i56.4917
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación y carga laboral como predictores de la autoeficacia profesional durante la Pandemia COVID-19 en docentes universitarios peruanos

Abstract: Introducción. Los docentes universitarios han tenido que enfrentar los cambios que demanda la educación virtual en tiempos de pandemia COVID-19. Por ello, se tuvo el objetivo de determinar si la adaptación a los medios académicos virtuales y carga laboral predicen la autoeficacia profesional en docentes universitarios. Método. Estudio asociativo-predictivo, donde participaron 321 docentes universitarios (55.5% varones y 44.5% mujeres) de dos universidades peruanas (22.4% estatal y 77.6% privada), de entre 26 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…While some studies have shown that a higher circumstantial workload can motivate workers (Baethge et al, 2018), generally, an excessive workload is associated with negative effects such as increased stress, burnout, and decreased quality of work (Aronsson et al, 2017). Therefore, in the context of the COVID-19 pandemic, the workload has shown a direct relationship with teachers' professional self-efficacy (Minaya-Herrera et al, 2022). Previous studies have confirmed that excessive workload and stress are related to teachers' professional selfefficacy (Topuzov et al, 2020;Eder-Karavaya et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While some studies have shown that a higher circumstantial workload can motivate workers (Baethge et al, 2018), generally, an excessive workload is associated with negative effects such as increased stress, burnout, and decreased quality of work (Aronsson et al, 2017). Therefore, in the context of the COVID-19 pandemic, the workload has shown a direct relationship with teachers' professional self-efficacy (Minaya-Herrera et al, 2022). Previous studies have confirmed that excessive workload and stress are related to teachers' professional selfefficacy (Topuzov et al, 2020;Eder-Karavaya et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The basis for this claim can be found in the findings of a study with Canadian teachers, demonstrating that those with higher stress due to workload had lower self-efficacy in performing their jobs (Klassen and Chiu, 2010). Additionally, two recent cross-sectional studies conducted during the health emergency analyzed the functional relationship between workload and professional self-efficacy, finding a significant negative correlation, the first among general university teachers (Minaya-Herrera et al, 2022), and the second among teachers in health science careers .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Otro estudio con base subjetiva realizado por Minaya et al (2022), utiliza un cuestionario con muestreo no probabilístico que permite establecer que la carga de trabajo incide en la autoeficacia en el ejercicio profesional de docentes universitarios en Perú. Así mismo, el estudio que realizan Martínez y González-Argote (2022), centrado en el personal de enfermería de un hospital público en Argentina, se basa en un cuestionario diseñado para medir la relación entre la sobrecarga de trabajo y la satisfacción de los colaboradores, sin embargo, los resultados evidencian mayor correlación entre la antigüedad laboral, las condiciones de trabajo y aspectos sociofamiliares con el estrés laboral.…”
Section: áRea De Registros Médicosunclassified